Fairness in practice a social contract for a global economy - James, Aaron (Oxford : Oxford University Press, 2012)
What would it be for the global economy to be fair? This book argues that 'structural equity' in an international practice of market reliance gives rise to significant egalitarian responsibilities. These require robust social insurance, capital controls, policy flexibility for developing countries, and more.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Fairness; International economic relations; Globalization